Single-step bioassays in serum and whole blood with a smartphone, quantum dots and paper-in-PDMS chips1. Issue 12 (21st June 2015) - Petryayeva, Eleonora; Algar, W. Russ
<x xml:space="preserve">Abstract</x> The optical properties of quantum dots permit single-step bioassays in whole blood using a custom chip and smartphone-based readout platform.